Kinetics experiments in ZED-2 using heterogeneous cores of advanced nuclear fuels. (November 2018) - Atfield, J.E.; Yaraskavitch, L.R.; Rand, E.T.
Highlights: Transient experiments were conducted using natural U/depleted U/Pu, Pu-Th, and 233 U-Th fuels. Inverse point-kinetics analyses were conducted for different methodologies and data libraries. The conventional groups used for photoneutrons do not accurately describe the transients. A 3D kinetics code which can appropriately treat photoneutrons is desired. Abstract: Neutronic transient measurements of substitution cores composed of low enriched uranium oxide driver fuel and uranium-plutonium (as simulated mid-burnup natural uranium), plutonium-thorium, or uranium-233-thorium mixed oxide fuels in a heavy water moderated lattice are presented. The measurements recorded flux at several detector locations outside the core while reactivity insertions of varying scale were conducted. The results provide valuable data to explore point and 3D reactor models. Inverse point-kinetics analyses of the recorded flux indicate that delayed parameters tabulated by only the fission-rate per nuclide provide similar results to adjoint-weighted kinetics parameters calculated by MCNP6 via the iterated fission probability method, on the timescale of delayed neutrons. However, the inadequacy of the conventional delayed photoneutron parameters, which are based on measurements of uranium-235 in D2 O, is clearly shown in the computed reactivity. The importance of delayed photoneutrons in heavy water reactor kinetics necessitates an improved understanding of the delayed photoneutron group structure by nuclide and appropriate adjoint-weighting for photoneutrons.